Reflections - Ravi Batra; BATRA (Ravi) (Pune: Progressive Prints, 1992)
Reflections is immense pleasure & thought - provoking. Gentle rhythm in the poems and lucid, tasteful expressions on themes which are undoubtedly laudable is soothing & rejuvenates one in one's otherwise busy & tension- ridden life." Shri Loknath Misra (Ex-Governor) Assam " In Reflections, the poet's sense of commitment to the readers as friend, philosopher and guide has found its pristine expression in each line of the poems impeccable style & chaste manner. Subjects addressed cover vast tapestry." Shri M V Dieghe (Ex Governor) Meghalaya
Keywords: English Poetry; English Literature